66. studentská vědecká konference Program a sborník abstraktů - Jurajda, Michal (Masaryk University Press, 2022)
Title in English: The 66th Student Scientific Conference: Programme and abstract book The publication contains overview of lectures that were presented at the 66th Student Scientific Conference, organised by the Faculty of Medicine on 8 November 2022.